Does GLP enhance the quality of toxicological evidence for regulatory decisions?. (3rd May 2016) - Borgert, Christopher J.; Becker, Richard A.; Carlton, Betsy D.; Hanson, Mark; Kwiatkowski, Patricia L.; Sue Marty, Mary; McCarty, Lynn S.; Quill, Terry F.; Solomon, Keith; Van Der Kraak, Glen; Witorsch, Raphael J.; Don Yi, Kun
Abstract: There is debate over whether the requirements of GLP are appropriate standards for evaluating the quality of toxicological data used to formulate regulations. A group promoting the importance of non-monotonic dose responses for endocrine disruptors contend that scoring systems giving primacy to GLP are biased against non-GLP studies from the literature and are merely record-keeping exercises to prevent fraudulent reporting of data from non-published guideline toxicology studies. They argue that guideline studies often employ insensitive species and outdated methods, and ignore the perspectives of subject-matter experts in endocrine disruption, who should be the sole arbiters of data quality. We believe regulatory agencies should use both non-GLP and GLP studies, that GLP requirements assure fundamental tenets of study integrity not typically addressed by journal peer-review, and that use of standardized test guidelines and GLP promotes consistency, reliability, comparability, and harmonization of various types of studies used by regulatory agencies worldwide. This debate suffers two impediments to progress: a conflation of different phases of study interpretation and levels of data validity, and a misleading characterization of many essential components of GLP and regulatory toxicology. Herein we provide clarifications critical for removing those impediments.